La suspensión de la ética en el malestar de la libertad: lo divino y el destino = The suspension of ethics in the discomfort of freedom: the divine and the destiny - Valentim, Inácio (Teocomunicação)
The purpose of this article is to demonstrate the ethical-practical conflict in the relation between the divine-fate and human beings. The incessant search for liberty and knowledge by human beings has been the principal factor in the suspension of the ethic. This freedom and wisdom invaded and disappropriated the exclusive space of the divine-fate resulting in the necessity for a new postcreation approach such as the fixed and contractual rules which will bind the human being to the divine-fate from now on